Adoption-specific therapy : a guide to helping adopted children and their families thrive - Waterman, Jill, 1945-; Langley, Audra; Miranda, Jeanne, 1950-; Riley, Debbie B. (American Psychological Association, 2018)
This manual presents a structured, evidence-based protocol for mental health treatment for families that adopt vulnerable children.